Pengaruh Store Atmosphere dan Promosi Terhadap Keputusan Pembelian Pada Toko Galaxy31 Computer Tasikmalaya - Dede Ilham Solehudin; Budhi Wahyu Fitriadi; Barin Barlian (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of store atmosphere and promotion on purchasing decisions at the Galaxy31 Computer Store in Tasikmalaya. The method used in this study is causality through a survey approach. With a research sample of 100 Consumers of the Galaxy31 Computer Store, Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Store Atmosphere and Promotion had a significant influence on Purchase Decisions at the Galaxy31 Computer Store. Partially Store Atmosphere has a significant influence on Purchase Decisions at the Galaxy31 Computer Store. Partially, promotions have a significant influence on purchasing decisions at the Galaxy31 Computer Store